Self-assembled carbon nitride sphere/sheet heterostructure for enhanced photocatalytic hydrogen generation - Soh, Zhen Yao (2017)
The consumption of fossil fuels as our daily energy source is not only depleting this non-renewable resource of energy and it also threatens our planet due to the production of greenhouse gases which brings about global warming. Many scientists have tried to harvest hydrogen, which is an alternative clean fuel through the use of photocatalytic water splitting. However, a highly efficient photocatalyst has yet to be developed despite decades of research and we are still looking for various ways to enhance the photocatalytic efficiency of such catalysts. One very attractive photocatalyst is g-C3N4, as it can be fabricated from earth-abundant materials and possesses a relatively low band gap. Unfortunately, it has poor photocatalytic performance due to high charge recombination, hence we aim to enhance the photocatalytic efficiency of g-C3N4 in this study.